Physical activity energy expenditure and cardiometabolic health in three rural Kenyan populations. Issue 1 (10th December 2018) - Lee, Jerry C.; Westgate, Kate; Boit, Michael K.; Mwaniki, David L.; Kiplamai, Festus K.; Friis, Henrik; Tetens, Inge; Christensen, Dirk L.; Brage, Soren
Abstract: Objectives: Physical activity is beneficial for metabolic health but the extent to which this may differ by ethnicity is still unclear. Here, the objective was to characterize the association between physical activity energy expenditure (PAEE) and cardiometabolic risk among the Luo, Kamba, and Maasai ethnic groups of rural Kenya. Methods: In a cross‐sectional study of 1084 rural Kenyans, free‐living PAEE was objectively measured using individually‐calibrated heart rate and movement sensing. A clustered metabolic syndrome risk score ( z MS) was developed by averaging the sex‐specific z ‐scores of five risk components measuring central adiposity, blood pressure, lipid levels, glucose tolerance, and insulin resistance. Results: z MS was 0.08 (−0.09; −0.06) SD lower for every 10 kJ/kg/day difference in PAEE after adjustment for age and sex; this association was modified by ethnicity (interaction with PAEE P < 0.05). When adjusted for adiposity, each 10 kJ/kg/day difference in PAEE was predicted to lower z MS by 0.04 (−0.05, −0.03) SD, without evidence of interaction by ethnicity. The Maasai were predicted to have higher cardiometabolic risk than the Kamba and Luo at every quintile of PAEE, with a strong dose‐dependent decreasing trend among all ethnicities. Conclusion: Free‐living PAEE is strongly inversely associated with cardiometabolic risk in rural Kenyans. Differences between ethnic groups in this association were observed but were explained by differences in central adiposity. Therefore, targeted interventions to increase PAEE are more likely to be effective in subgroups with high central adiposity, such as Maasai with low levels of PAEE.